2021
DOI: 10.1186/s12879-020-05672-6
|View full text |Cite
|
Sign up to set email alerts
|

ODYSSEY clinical trial design: a randomised global study to evaluate the efficacy and safety of dolutegravir-based antiretroviral therapy in HIV-positive children, with nested pharmacokinetic sub-studies to evaluate pragmatic WHO-weight-band based dolutegravir dosing

Abstract: Background Dolutegravir (DTG)-based antiretroviral therapy (ART) is highly effective and well-tolerated in adults and is rapidly being adopted globally. We describe the design of the ODYSSEY trial which evaluates the efficacy and safety of DTG-based ART compared with standard-of-care in children and adolescents. The ODYSSEY trial includes nested pharmacokinetic (PK) sub-studies which evaluated pragmatic World Health Organization (WHO) weight-band-based DTG dosing and opened recruitment to child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 17 publications
4
34
0
Order By: Relevance
“…Even as newer medications with high barriers to resistance are rolled out for CAWH (e.g. second‐generation integrase strand transfer inhibitors), scale‐up challenges in the context of implementation, prior relevant ART exposures, and limited availability of formulations may still negatively affect the trajectory and impact of resistance [15]. Largely unknown aspects of resistance (e.g.…”
mentioning
confidence: 99%
“…Even as newer medications with high barriers to resistance are rolled out for CAWH (e.g. second‐generation integrase strand transfer inhibitors), scale‐up challenges in the context of implementation, prior relevant ART exposures, and limited availability of formulations may still negatively affect the trajectory and impact of resistance [15]. Largely unknown aspects of resistance (e.g.…”
mentioning
confidence: 99%
“…The ODYSSEY trial was an open-label, multicentre, randomised, controlled, non-inferiority trial that evaluated the 96-week efficacy and safety of dolutegravir plus two nucleoside reverse transcriptase inhibitors versus standard of care in 792 children living with HIV, aged from 4 weeks to younger than 18 years, starting first-line or second-line ART in Africa, Europe, and Thailand. 10 ODYSSEY included two randomised cohorts: the main trial enrolled 707 children with bodyweight of 14 kg or greater, 11 and an additional randomised cohort enrolled 85 children with bodyweight from 3 kg to less than 14 kg. 12 Most children from Thailand and Africa in the main trial (613 [94%] of 652 children) and in the cohort with bodyweight of less than 14 kg (70 [95%] of 74) continued in ongoing observational follow-up after completion of the randomised phase, with additional consent.…”
Section: Methodsmentioning
confidence: 99%
“…ODYSSEY is an open-label, randomised, parallel-group, non-inferiority trial comparing dolutegravir plus two nucleo side or nucleotide reverse transcriptase inhibitors (NRTIs; dolutegravir arm) versus standard of care (NNRTI, boosted protease inhibitor, or non-dolutegravir integrase inhibitor, plus two NRTIs) in infants, children, and adolescents with HIV (younger than 18 years), starting first-line ART (ODYSSEY-A) or switching to second-line ART after treatment failure with first-line regimens (ODYSSEY-B). 14 The main trial recruitment period was between Sept 20, 2016 and June 22, 2018 and was open to children weighing at least 14 kg, with children weighing less than 14 kg ineligible for random assignment during this period due to absence of an appropriate dolutegravir formulation and dosing for weight bands lower than 14 kg. Recruitment of children weighing less than 14 kg opened on July 5, 2018 using a 5 mg dispersible tablet with dosing based on preliminary IMPAACT P1093 data.…”
Section: Methodsmentioning
confidence: 99%
“…8,9,[11][12][13] The ODYSSEY trial aimed to compare the efficacy and safety of dolutegravir-based ART versus standard of care in children starting first-line or secondline ART. 14 The main trial recruited children weighing at least 14 kg and showed superiority of dolutegravir-based ART. 15 Based on a nested pharmacokinetic and safety substudy, 16 the US Food and Drug Administration (FDA) and European Medicines Agency approved the adult 50 mg dolutegravir dose in children weighing 20 kg or more.…”
Section: Introductionmentioning
confidence: 99%